Corporate social disclosure in Shell Malaysia Berhad corporate reports 1968-2003: Pursuing for corporate legitimacy or managing reality? - Abdul Rahman, Azhar; Mohd Nasir, Mohd Herry; Abdul Aziz, Norazita Marina; Shaari, Hasnah (2007)
This paper examines the nature of corporate social reporting (CSR) in the annual reports of a company in Malaysia and tries to explain whether the changes in disclosure level do conform with legitimacy theory. The published annual corporate reports of the multinational company, Shell Malaysia Berhad are analyzed over the period 1968-2003 inclusive with a view to providing insight into the causes of variability in CSR. Using content analysis, word counts measurement was employed to provide a more intensive method of data capture. The paper finds that whilst the expected upward trend in CSR is notable, the more interesting feature is the variability in disclosure between chairmen's terms in office. It is argued that the fluctuations in the levels of disclosure can be explained by the varying perceptions of reality of the successive chairmen. The legitimacy theory only partly explains the variability in CSR disclosure.